Understanding How Data Triangulation Identifies Acute Toxicity of Novel Psychoactive Drugs - Wood, D. M. (Springer-Verlag, 2012)
Over the last decade, there has been an increase in the availability and use of novel psychoactive substances (also known as “legal highs”). There is limited information available on the potential acute toxicity (harms) associated with the use of these novel psychoactive substances. Gold standard evidence, such as animal studies or human clinical trials, is rarely available to users or healthcare professionals. However, it is possible to use triangulation of data on the acute toxicity from multiple sources to describe the overall pattern of toxicity associated with a novel psychoactive substance. In this review, we will describe these potential data sources, which include self-reported toxicity on internet discussion fora, data from sub-population user surveys, data from regional and national poisons information services and published case reports and case series. We will then describe how pattern of acute toxicity associated with the use of the cathinone mephedrone (4-methylmethcathinone) was established using triangulation of these different data sources.